Umbilical abscess as a rare cause of abdominal pain: A case report - Hiroshi Ito (Journal of Acute Disease)
Rationale: Abdominal pain is a common complaint with a broad differential diagnosis, including both intra-abdominal and abdominal wall pathologies. While visceral causes are frequently considered, abdominal wall conditions are often overlooked, leading to diagnostic delays. Among them, umbilical abscesses are rare but require distinction from urachal abscesses due to differences in management. Patient’s concern: A 46-year-old woman presented with a one-week history of periumbilical pain unresponsive to analgesics. Diagnosis: Physical examination revealed localized tenderness and a positive Carnett’s sign. Computed tomographic images identified an umbilical abscess without evidence of urachal remnants, ruling out a urachal abscess. Interventions: The patient underwent abscess drainage and received cefalexin (1500 mg/day) for 28 days. Outcomes: The abscess resolved completely without recurrence. Lessons: Umbilical abscesses are rare and may be mistaken for urachal abscesses. A thorough clinical evaluation, including Carnett’s sign and imaging studies, is crucial for accurate diagnosis. Prompt differentiation facilitates appropriate management and prevents unnecessary interventions.